2007
DOI: 10.1021/la702690a
|View full text |Cite
|
Sign up to set email alerts
|

Liposome-Recruited Activity of Oxidized and Fragmented Superoxide Dismutase

Abstract: The peptide fragment of H2O2-treated Cu,Zn-superoxide dismutase (SOD) was found to be reactivated with liposomes prepared by 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphocholine (POPC). The fragmentation of SOD was observed by 2 mM H2O2 treatment as well as by SOD inactivation and the loss of an alpha-helix in the neighborhood of its activity center. The H2O2-treated SOD, which lost its activity at different incubation times, was dramatically reactivated only by adding POPC liposomes, resulting in 1.3-2.8 times hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 29 publications
1
27
0
Order By: Relevance
“…"raft" domains) in cells has attracted much attention because of its implications for membrane-related processes, including bacterial and viral infections and signal transductions [22]. Recent studies have also revealed that the lipid membranes can activate the biomacromolecules and regulate their functions [6][7][8][9][39][40]. Liposomes have been intensely studied as a biomimetic environment of lipid bilayers.…”
Section: "Liposome Membrane Design" For Recognition Of Biomacromoleculesmentioning
confidence: 99%
See 2 more Smart Citations
“…"raft" domains) in cells has attracted much attention because of its implications for membrane-related processes, including bacterial and viral infections and signal transductions [22]. Recent studies have also revealed that the lipid membranes can activate the biomacromolecules and regulate their functions [6][7][8][9][39][40]. Liposomes have been intensely studied as a biomimetic environment of lipid bilayers.…”
Section: "Liposome Membrane Design" For Recognition Of Biomacromoleculesmentioning
confidence: 99%
“…A liposome membrane is effective in its use as a platform to perform the above purpose because it looks after the fundamental characteristics of a conventional extraction system and the recognition surface of the biomolecule ( Figure 1). In practice, there are many reports on the possible role of a liposome membrane to recognize various molecules , such as asymmetric recognition [56-57], metal affinity [4], peptide recognition [7,58], enzyme-like function [8,59], RNA recognition [6,42,48], and others [9,28] (Figure 8). membrane modules [61], and hydrogel immobilization of the liposomes at high concentration ( Figure 9) [62].…”
Section: Conclusion and Future Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Emergent properties arising from the membrane of the liposome (vesicle) have been introduced, where the vesicle (liposome) membrane can selectively interact with various types of molecules under particular conditions. 12 The important functions of vesicles include (1) interaction with proteins (enzymes) and nucleotides, [13][14][15][16][17] (2) storage of encapsulated molecules, 1,18 and (3) fusion with membranes. 19 Vesicle membranes are dynamic, for example, vesicles composed of 1,2-dimylistoyl-sn-glycero-3-phosphocholine (DMPC) and 1,2-dipalmitoyl-sn-glycero-3-phosphocholine (DPPC) possess phase transition temperatures (T m ) at 23.6 and 41.…”
Section: Introductionmentioning
confidence: 99%
“…There have been several studies on the up-or down-regulation of the function of the gene expression machinery [5], RNA [6], peptides [7] and enzymes [8] and hydrophobic interactions [9][10]. However, each contribution requires investigation in a simpler target molecule.…”
Section: Introductionmentioning
confidence: 99%